Micrometric measures and orbits of southern visual double stars. Issue 4 (June 2015) - Argyle, R. W.; Alyner, A.; van Leeuwen, F.
Abstract 525 measures of 213 visual double stars have been made using the 26.5‐inch (67‐cm) Innes telescope in Johannesburg and the Repsold micrometer between 2008.375 and 2008.419, 2010.608 and 2010.652, and 2013.663 and 2013.712. A comparison with known orbits is made. Revised orbits are presented for WDS 01061–4643 (SLR 1), WDS 12415–4858 (HJ 4539), WDS 16253–4909 (COO 197) and WDS 16425–3705 (R 283). (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)